Comportamiento de la balanza de pagos de ecuador antes y después de la dolarización: durante el período 1994-2010 - Toapanta Cando, Mercedes Natali (2022)
The current research project has as aim to analyze the behavior from Ecuador’s payments balance before and after dollarization: during the 1994-2010 period, through the explanatory variables study, such as the gross domestic product, inflation, public external debt, real exchange rate and as explained variable the current account without oil goods. For this, it was applied a methodology with a research quantitative approach and a descriptive level that allowed analyzing the variables behavior and evolution, which intervene in the payments balance current account, with data from quarterly frequency time series, as well as, it was used a documentary-bibliographical design to collect information about the variables, applying a multiple linear regression model and a Granger causality model. Among the results, it was got, what the multiple linear regression model indicates, which the variables considered explain the current account by 0.9004, with inflation and gross domestic product as significant variables, since they do not exceed 5% probability, while the debt external public with 97.04% and real exchange rate with 54.93% are not significant. On the other hand, the Granger causality model reinforced the got results previously, indicating that there is a current account bidirectional causality with the significant variables, that is, they cause each other. Among the most relevant conclusions, it was evidenced, what Ecuador demonstrated from 1994 to 1999 constant refinancing of the external public debt, increasing inflation and currency devaluation, while from 2000 to 2010, it demonstrated debt refinancing, decreasing inflation and stable real exchange rate type. Similarly, it can be mentioned, which the real exchange rate is not significant for the current account without oil goods, that is, even if Ecuador had not been dollarized, the payments balance would still be negative.